Early upper paleolithic colonization across Europe: Time and mode of the gravettian diffusion - Bicho, Nuno Gonçalo Viana Pereira Ferreira (2018)
This study presents new models on the origin, speed and mode of the wave-of-advance leading to the definitive occupation of Europe's outskirts by Anatomically Modern Humans, during the Gravettian, between c. 37 and 30 ka ago. These models provide the estimation for possible demic dispersal routes for AMH at a stable spread rate of c. 0.7 km/year, with the likely origin in Central Europe at the site of Geissenklosterle in Germany and reaching all areas of the European landscape. The results imply that: 1. The arrival of the Gravettian populations into the far eastern European plains and to southern Iberia found regions with very low human occupation or even devoid of hominins; 2. Human demography was likely lower than previous estimates for the Upper Paleolithic; 3. The likely early AMH paths across Europe followed the European central plains and the Mediterranean coast to reach to the ends of the Italian and Iberian peninsulas.